Peran Serangga sebagai Vektor Penyakit Karat Puru pada Sengon (Albizia falcataria L. Fosberg) - Triyogo, Ananto (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Sengon (Albizia falcataria L. Fosberg) forest plantations of community in Wonosobo District, Central Java were attacked by gall rust disease. The objective of this research was to investigate the role of insects as a vector of gall rust disease. The attack intensity was measured in the different ages of tree stand (1, 2, 3, 4, and 6 year old) with randomized complete block design (RCBD) consisting of 3 blocks, 3 replications, and 3 sampling plots. The role of insect as a vector was tested using two different approaches: observation on the spores in the adult insect integument and artificial investation of insect containing spores on the healthy seedlings. The result of this research showed that the one year old of sengon had highest disease intensity (95.5%) and lowest disease incidence (56.96%). The identification showed that the insect belongs to Lepidoptera (Family Heliozelidae) completing the metamorphosis in the gall. Spores were found in the integument of Lepidoptera (Family Heliozelidae) at the average of 2.8 x 104 spore μL-1 insect-1. Artificial innoculation on healthy seedling did not show the infection symptoms by Uromycladium tepperianum until 5 weeks after innoculation.